Efficacy of perioperative esketamine on postoperative depression: a systematic review and meta-analysis - Li, Hao-Yan; Xu, Wen-Jing; Wang, Ya-Mei; Xie, Shuang; Wang, Huan-Liang (Frontiers in Psychiatry, 2025)
BackgroundPostoperative depression (POD) represents a serious complication in surgical patients, exacerbating morbidity and mortality rates while imposing a substantial economic burden on healthcare systems. Despite its widespread clinical use, the role of esketamine, an NMDA receptor antagonist with rapid antidepressant effects, remains understudied in perioperative settings. Therefore, we conducted a systematic review and meta-analysis to assess the efficacy of esketamine on postoperative depression. To evaluate the effect of esketamine on the incidence and severity of postoperative depression in different types of surgery by randomized controlled trial, investigate whether esketamine can effectively reduce the postoperative depression score and the incidence of postoperative depression in the short and long term after use, to promote the application of perioperative analgesia-antidepressant combination.MethodSearched PubMed, the Cochrane Library, the Web of Science, and Medline to identify randomized controlled trials using the drug of esketamine and analyzed the data using Review Manager 5.3.ResultsWe included a total of 8 randomized controlled trials involving 1724 patients who met the criteria. The meta-analysis revealed that esketamine treatment, compared with control groups, significantly reduced POD. Improvements were observed at 1 week (RD -0.09, 95% CI [-0.13, -0.05], P < 0.0001, I²=84%), 2 weeks (RD -0.08, 95% CI [-0.13, -0.03], P < 0.00001, I²=97%), and long-term follow-up (RD -0.06, 95% CI [-0.10, -0.02], P=0.0002, I²=79%).ConclusionEsketamine demonstrates efficacy in reducing POD incidence and severity, although its use is associated with an increased risk of adverse effects. Also, the method of drug injection, the duration of administration and the number of doses may have an effect on the results. Therefore, further exploration of appropriate dosing regimens and multi-modal strategies is necessary to mitigate adverse effects.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024506329.